The relationship between Japanese adults’ age and self-reported verbal strategies when lying - Tabata, Naoya; Vrij, Aldert (Frontiers in Psychology, 2023)
We examined the relationship between age and self-reported verbal deception strategies in Japanese adults. Japanese participants (N =153) aged 18 to 73 years took part in this study. We requested the participants to state their age and freely describe how they structure their speech to appear convincing when lying during their daily interactions. We extracted 13 verbal strategies from the participants' open-ended descriptions. Japan is a high-context culture. The results indicated that 11 categories corresponded to the verbal strategies reported in previous studies on lying conducted in low-context cultures. However, two strategies mentioned in the current study, making ambiguous statements and adding irrelevant details to the lie, were not reported in low-context cultures. As expected, age was significantly and negatively correlated with the number of verbal strategies used when lying. Moreover, verbal strategies that seem relatively cognitive demanding were used less as the age of the participants increased. We concluded that these results reflected the age-related decline of cognitive abilities.